Inovasi Pembelajaran Kuantum Guna Membangun Kompetensi Abad 21 - Alindra, Afridha Laily; Rahmania, Cici Aulia; Ambarwati, Desti Noer; Luhukay, Michelya Zabrina; Alfiyyah, Ravina Azhar; Haryanti, Sri; Janah, Zahra Wardatul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Quantum Learning is a learning model that brings students to activities. Technological advancement is known as the 21st century era. The demands of global progress have changed the paradigm of teacher-centered learning into new student-centered learning. The four basic competencies that must be possessed in the 21st century are Critical thinking, Creativity, Communication, and Collaboration. The method used in this research is qualitative with an interview and documentation approach, using oral questions and oral answers, plus documentation that serves as supporting data so that the results can be considered valid. The results showed that in phase A, phase B, and phase C, quantum learning had been applied which included giving awards and praise to students. In phase A, contextual learning was done through concrete media. While in phases B and C, teachers try to relate the subject matter to students’ real experiences. For competency-related learning, the school provides worship facilities for all religions, so that students gain an understanding of tolerance. This is certainly in line with some of the skills needed in the 21st century, such as critical thinking, collaboration, creativity and communication. In this way, it is hoped that there will be an improvement in learning innovation at the primary school level.